Source analysis and health risk assessment of polycyclic aromatic hydrocarbons in atmospheric PM2.5 in a district of Taizhou City from 2019 to 2021 - Yanqiu ZHANG; Guang YU; Wei WANG; Li HANG; Qian WANG; Li WANG; Qiuju QIAO; Jiuhong HUANG (环境与职业医学, 2024)
BackgroundPolycyclic aromatic hydrocarbons (PAHs), one of the main components of fine particulate matter (PM2.5), have a certain impact on ambient air quality, and long-term exposure to PAHs may pose potential health risks to human beings. ObjectiveTo identify the distribution characteristics and sources of PAHs in atmospheric PM2.5 in a district of Taizhou City from 2019 to 2021, and to evaluate the health risks of PAHs to the population in the area through the inhalation pathway. MethodsFrom 2019 to 2021, air PM2.5 sampling was carried out at a state-controlled surveillance point in a district of Taizhou City for 7 consecutive days on the 10th-16th of each month, the sampling time was 24 h·d−1, and the sampling flow rate was 100 L·min−1. PM2.5 mass concentration was calculated by gravimetric method. A total of 16 PAHs were determined by ultrasonic extraction-liquid chromatography. Kruskal-Wallis H test was used to compare the distribution charac teristics of PAHs concentrations by years and seasons, characteristic ratio and principal component analysis (PCA) was used to analyze their sources, and a lifetime carcinogenic risk (ILCR) model was used to assess the health risk of PAHs. ResultsFrom 2019 to 2021, the annual average concentrations [M (P25, P75)] of ∑PAHs in atmospheric PM2.5 in the selected district of Taizhou City were 6.52 (2.46, 10.59), 8.52 (4.56, 12.29), and 3.72 (1.51, 7.11) ng·m−3, respectively, and the annual benzo[a]pyrene (BaP) excess rates (national limit: 1 ng·m−3) were 27.38% (23/84), 47.62% (40/84), and 19.04% (16/84), respectively, both presenting 2020> 2019 > 2021 (P<0.001, P<0.05). The ∑PAHs concentration distribution showed a seasonal variation, with the highest value in winter and the lowest value in summer (P<0.05). Among the atmospheric PM2.5 samples, the proportion of 5-ring PAHs was the highest, the proportion of 2-3-ring PAHs was the lowest; the proportion of 2-4-ring PAHs showed a yearly upward trend, and the proportion of 5-6-ring PAHs showed yearly downward trend (P<0.05). The characteristic ratio and PCA results suggested that the sources of sampled PAHs were mainly mixed sources such as dust, fossil fuel (natural gas), coal combustion, industrial emissions, and motor vehicle exhaust emissions. The ILCR (RILCR) of PAHs by inhalation for men, women, and children were 1.83×10−6, 2.35×10−6, and 2.04×10−6, respectively, and the annual average RILCR was 2.07×10−6, all greater than 1×10−6. ConclusionFor the sampled time period, the main sources of PAHs pollution in atmospheric PM2.5 in the target district of Taizhou City are dust, fossil fuel (natural gas), coal combustion, industrial emissions, motor vehicle emissions, etc., and PAHs may have a potential carcinogenic risk to local residents.